ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETIMPANGAN DISTRIBUSI PENDAPATAN DI PULAU JAWA TAHUN 2014-2020 - Resta Dwi Andina; jajang Jajang; Supriyanto Supriyanto (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2021)
Unequal distribution of income is one indicator of community welfare. Improving and equalizing the standard of living people in various regions is one of the efforts to realize national economic development. The existence of an unequal distribution of income also has an impact on economic development. This study discusses panel data regression analysis to determine the factors that affect the unequal distribution of income in Java from 2014 to 2020 with the help of Eviews 10 software. The factors that are thought to affect unequal distribution of income in this study are the Human Development Index (HDI), Open Unemployment Rate (OPR), Regional Gross Domestic Product (RGDP) per capita, and total of poor people. The fixed effects model (FEM) was chosen to be the best model. The results showed that the HDI and RGDP per capita variables had negative and significant effect on unequal distribution of income in Java from 2014 to 2020.